Appropriate aspirations for effective post-mining restoration and rehabilitation: a response to Kaźmierczak et al. - Cross, Adam; Young, R.; Nevill, Paul; McDonald, Tein; Prach, K.; Aronson, J.; Wardell-Johnson, Grant; Dixon, Kingsley (Springer, 2018)
Confusion surrounding the definition and application of terminology in post-mining ecological repair has resulted in uncertainty for industry, the scientific community and regulators. This lack of clarity may underrepresent high aspirations or could be misused to disguise low aspirations and so is problematic for setting objectives, establishing goals and assessing recovery trajectories. We respond to a recently published analysis of the ecosystem repair literature, where we highlight inconsistencies stemming from inadequate reference to a large proportion of the restoration and rehabilitation literature. We outline increasingly well-accepted and internationally applied definitions concerning the restoration and recovery process and invite both the mining industry and policy-makers to re-examine their terminology in the interests of attaining an internationally agreed nomenclature. Clarity in the use and understanding of terminology will align post-mining targets with community expectation, enhance the capacity of the mining industry to understand and meet these targets, and foster better analysis and more industry-relevant discussion of recovery methodologies by the scientific community and practitioners.